Commoning Water: Experiential Learning Tools to Strengthen Water Governance - Meinzen-Dick, Ruth S.; Priyadarshini, Pratiti; Singh, Subrata; Mittal, Rajesh; Falk, Thomas; Mittal, Rajesh (2022)
Ruth Meinzen-Dick, Pratiti Priyadarshini, Subrata Singh, Rajesh Mittal, and Thomas Falk Meinzen-Dick, Ruth; Priyadarshini, Pratiti; Singh, Subrata; Mittal, Rajesh, and Falk, Thomas. 2022. Commoning Water: Experiential Learning Tools to Strengthen Water Governance. PowerPoint presentation given during the Wednesdays for Water Forum, November 23, 2022 (virtual)